Heat transfer enhancement in two-phase microchannel heat exchangers for high heat flux electronics - Hoke, Jensen, author; Bandhauer, Todd, advisor; Windom, Bret, committee member; Venayagamoorthy, Karan, committee member (Colorado State University. Libraries, 2020)
Laser diodes are semiconductor devices that emit high intensity light with a small spectral bandwidth when a forward voltage is applied. Laser diodes have a high electrical to light conversion efficiency which can be greater than 50%. These robust, high efficiency laser sources are used in medical and manufacturing fields and, if their power can be increased, show promise in inertial confinement fusion and defense applications. Individual diode emitters are arrayed into bars with a footprint of 1 mm by 10 mm to increase their light output power. These bars are further combined into arrays with the light emitting edges stacked close together. As the spacing in these arrays are reduced to increase brightness, thermal management becomes the limiting factor for each bar. State of the art diode arrays can have heat fluxes exceeding 1 kW cm-2. Effective thermal management strategies are key because the diode's output wavelength, bandwidth, efficiency and lifetime are temperature dependent. Commercially available high powered laser diode arrays are traditionally cooled using a single-phase fluid passing through conduction coupled copper-tungsten channels. These heat exchangers have high thermal resistances which require the coolant to be significantly subcooled before entering the device. High working fluid flow rates are required to reduce thermal gradients in the diode bars and working fluid conditioning is required to reduce corrosion in the cooling plates. Many of these issues can be addressed by cooling the diodes with a two-phase working fluid in a corrosion resistant, silicon microchannel heat exchanger. The high heat transfer coefficients associated with flow boiling, as well as the high surface area to volume ratios in microchannel arrays allow the working fluid temperature to be much closer to that of the diode which reduces the cooling load on a system level. Additionally, as heat is added to a two-phase fluid, there is virtually no change in temperature. Therefore, the working fluid flow rate can be much lower than a comparable single-phase heat exchanger, which reduces pump work. However, using a two-phase working fluid presents its own unique set of challenges. This work presents a novel approach to increasing the effective critical heat flux and reducing thermal resistance in an array of 125 high aspect ratio silicon microchannels (40 µm × 200 µm) subjected to heat fluxes up to 1.27 kW cm-2. R134a is used as the two-phase working fluid and outlet vapor qualities up to 80.7% are reported. The silicon heat exchangers are manufactured using a DRIE MEMS process that allows fine control over feature sizes. The performance of traditional plain walls is compared to a novel sawtooth structuring pattern that increases available heat transfer area by 41% and provides bubble nucleation sites. A 17% decrease in thermal resistance is reported for one of the area enhancement schemes and critical heat flux is increased in both area enhanced parts. A thermal FEA model is used to determine heat transfer coefficients and local heat fluxes within the test section. This model is used to investigate alternate patterning schemes. An adjustment to the Bertsch two-phase heat transfer coefficient is also suggested for smaller microchannels geometries and higher heat fluxes. Examination of the model results show that performance increase observed in the area enhanced test sections is driven by an increase in bubble nucleation sites. The additional area available for heat transfer has little effect because reduction of heat flux at the fluid wall interface reduces two-phase heat transfer coefficients. This effect is driven by the relative importance of nucleate boiling in these small channels.
Keywords: microchannel; boiling; two-phase